Toward a New Era of Fetal Tobacco Syndrome - Ino, Toshihiro; Kurosawa, Kazuo (International Journal of Pediatrics and Child Health, 2014)
Fetal tobacco syndrome (FTS) was first reported in early 1986. However, since that time, neither the name nor diagnostic criteria of the disease have been applied. One reason for this is that bronchial asthma, sudden infant death syndrome, attention deficit hyperactive syndrome and obesity as delayed symptoms of FTS, are not found at birth. The initial diagnostic criteria include: (1) maternal smoking with a cigarette consumption of more than five cigarettes/day during pregnancy, (2) symmetrical developmental delays with no other causes (gestational age ?37 weeks and birth weight< 2,500 g), (3) no maternal hypertension. However, a low birth weight at a gestational age of less than 37 weeks, congenital malformations and delayed symptoms should also be included in these diagnostic criteria. In this review, FTS is compared with fetal alcohol syndrome and new diagnostic criteria are proposed based on previous reports.